Implementasi Model Scramble dalam Pembelajaran Mengidentifikasi Informasi pada Teks Deskripsi Kelas VII di MTSs Al-Ikhlas Bilungala - Olii, Fahjihan Titania; Salam, Salam; Sartika, Eka (Ideas: Jurnal Pendidikan, Sosial dan Budaya, 2025)
This study was motivated by the need for innovation in teaching methods to improve students' ability to identify information in descriptive texts. At MTs Al-Ikhlas Bilungala, conventional teaching approaches often failed to motivate students, resulting in their low understanding of the material. The Scramble learning model was chosen because it is considered capable of creating an interactive, collaborative, and enjoyable learning atmosphere to address these challenges. This study aims to describe the planning, implementation, results, as well as the supporting and inhibiting factors in using the Scramble model for teaching the identification of information in descriptive texts in Grade VII at MTs Al-Ikhlas Bilungala. Using a qualitative descriptive method, data were collected through observation, interviews, documentation, and tests. The findings reveal that the lesson planning was designed for two meetings, its implementation followed the prepared lesson plans (RPP), and the results showed an increase in students' scores from an average of 65 in the pre-test to 80 in the post-test, with 80% of students meeting the minimum mastery criteria. The supporting factors in the learning process include interactivity, collaboration, and the use of diverse roles, while the inhibiting factors involve varying levels of student participation and difficulties in understanding texts. Overall, the Scramble model proved effective in improving students' understanding, despite some challenges that need to be addressed.